05 The cardioprotective effect of mildronate is associated with decreased CPT I-dependent fatty acid metabolism in mitochondria. Issue 24 (24th November 2011) - Kuka, J; Makrecka, M; Vilskersts, R; Dambrova, M
Abstract : Mildronate is a cardioprotective agent whose mechanism of action is based on decrease in L-carnitine concentration in heart tissue and concomitant decrease in fatty acid metabolism. The present study was undertaken to highlight the role of mitochondrial energy pathways in the anti-infarction mechanism of mildronate. Male Wistar rats received water or mildronate (100 mg/kg, orally) for 14 days. The isolated rat heart ischaemia-reperfusion injury study was performed based on Langerdorff technique. L-carnitine concentration and carnitine palmitoyltransferase I (CPT I) dependent or independent mitochondrial respiration were measured. In addition, the effect of cytochrome c on respiration of saponin-permeabilised cardiac ventricular fibres isolated from ischaemic hearts was determined. Mildronate treatment induced a significant threefold decrease in the L-carnitine concentration in heart tissue and decreased infarct size by 38%. Treatment with mildronate decreased CPT I-dependent mitochondrial respiration on palmitoyl-CoA by 27%, while it had no effect on CPT I-independent respiration on palmitoylcarnitine. Mildronate treatment significantly diminished the ischaemia-induced respiration stimulation by exogenous cytochrome c when pyruvate/malate and succinate were used as respiratory substrates. In conclusion, our results provide evidence that the anti-infarction activity of mildronate is related to decrease in CPT I-dependent fatty acid metabolism. The cardioprotective effect of mildronate could be partially attributed to the maintenance of the integrity of mitochondrial outer membrane.